Resource planning electronic board for agriculture industry application model - Hani Syairah, Azman (2008)
The agriculture sector registered favorable growth during the Eight Malaysia Plan period. Export earnings of the sector expanded significantly due to the increase in export volume and better prices of agricultural industrial commodities. During the Ninth Plan period, the overall policy thrusts of the agriculture sector will focus on its reorientation towards greater commercialization and the creation of high-income farmers as well as promotion of greater private sector investment including foreign investment. In order to fulfill the Ninth Plan policy, various steps must be made to help the farmer plan their resources for agriculture industry application. As we know, in ggriculture fields products need to be harvested or must be maintained by the farmers regularly but the labor used daily could be from a different team. So that, we could design a tree indicator link back to display on electronic board (say to be placed at a hut/small office) as centralized monitoring or resource planning enable the farmer’s activities or schedule to be followed more systematic. This resource planning will transmit the input data from the three types of sensors and the input data are types of activities done by the farmers. After the receiver part of the microcontroller receive the data from the transmitter part, the data will be displayed on the electronic board which areas of the farmers have done their activities. The activities of the farmers are including fertilizing, pouring water, and poisoning. So that, in the other visit, the other labor team knows which areas have not been treat by the farmers yet. This resource planning is using a Microchip PIC18F4550 microcontroller and several sensors as their input devices such as NPK sensor (fertilizer), acidic sensor which is pH sensor (weed poison like herbicide) and soil moisture sensor.